Silica Fume as Precursor in the Development of Sustainable and High-Performance MK-Based Alkali-Activated Materials Reinforced With Short PVA Fibers - Batista, Raquel P.; Trindade, Ana Carolina C.; Borges, Paulo H. R.; Silva, Flávio de A. (Frontiers in Materials, 2019)
Alkali-activated materials (AAM) are currently the subject of increasing interest and research, mainly due to the possibility to reduce the carbon dioxide (CO2) emissions in their production when compared to Portland cement (PC) and still achieve superior performance in many aspects when compared to traditional PC-based products. However, the use of sodium silicate (SS) as an alkaline activator in AAM is controversial when the aim is to reduce the environmental impact, as the production of the first also releases significant amount of CO2 per ton of activator produced. Therefore, a demand has emerged for alternative silica-rich materials that could effectively reduce the demand for SS without compromising the mechanical behaviour of the matrices and consequently the performance of fibre reinforced AAM. This paper investigates the gradual replacement (0% to 18% wt.) of metakaolin (MK) with silica fume (SF) in PVA-reinforced AAM, allowing the reduction of SS in the activator, also containing NaOH. Matrices with different composition were studied, i.e. with [SiO2]/[Al2O3] molar ratios of 3.0 and 3.8. All formulations were reinforced with 2% vol. of PVA fibres. The mechanical properties investigated were compressive strength, modulus of elasticity, flexural strength and toughness. Apparent dry density, water absorption and porosity of the composites were also assessed to give an indication of their durability. Single fibre pullout, fracture toughness and direct tensile tests were also carried out in order to understand the deformation capability of the composites. Results indicated that the employment of SF may effectively reduce the demand for SS in the alkaline activators, in order to produce alkali-activated composites with lower environmental impact (reduced CO2 emissions). Adjustments in the formulations may improve toughness in flexion in 170% with 30 wt.% reduction of SS in the activator, as well as improvements in deformation capability in tension. The development of strain-hardening MK-based AAM, however, has some challenging aspects that are also discussed.